Sistem kendali dan pemantauan penggunaan listrik berbasis IoT menggunakan Wemos dan aplikasi Blynk - Mardhiya Hayaty; Ade Rufaidah Mutmainah (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2019)
This study aims to apply the Internet of Things (IoT) technology to control electronic devices and monitor the electrical power usage remotely via the Internet. The system was implemented using Wemos D1, ACS712 current sensor, relay, and the Blynk application as the system interface on the smartphone. The system used an average of 0.4-3.3 seconds to respond to commands from the Blynk application via a Wifi connection at a distance of 50-1000 meters and the device control and power monitoring system can function properly. The system response time was not affected by distance. This system with Wifi access can be an alternative to control devices and monitor their power usage in addition to a longer time of SMS access and shorter range of Bluetooth.